2015
DOI: 10.1002/2014ja020780
|View full text |Cite
|
Sign up to set email alerts
|

An unusual sequence of sprites followed by a secondary TLE: An analysis of ELF radio measurements and optical observations

Abstract: We present an extraordinary case of sprites in rapid succession-four sprite clusters in only 400 ms -followed by a secondary jet. Simultaneous ELF and optical observations, as well as lightning data, enabled us to thoroughly document this unique event. Locations of the transient luminous events (TLEs) were triangulated using video recordings from Nydek (Czech Republic) and Sopron (Hungary). We found that sprites were displaced up to 70 km from their parent lightning. The current moment waveform and charge mome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 65 publications
1
50
0
Order By: Relevance
“…They can also last longer times as observed, for example, in Mlynarczyk et al . [] and Füllekrug et al . [] with a few tens of milliseconds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can also last longer times as observed, for example, in Mlynarczyk et al . [] and Füllekrug et al . [] with a few tens of milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported pulse‐shaped current signature related to sprites, in particular, when they are very bright [ Cummer et al ., ; Füllekrug et al ., ; Hu et al ., ; Soula et al ., ; Mlynarczyk et al ., ]. Figure displays the electric field radiated in ELF/VLF/LF (upper/central/lower graphs) during 120 ms, 25 ms before, and 95 ms after the SP + CG in both cases of series of dancing sprites: (a) at 1803:10.123 UTC that corresponds to the brightest sprite element in F62 of Figure a and (b) at 1808:20.899 UTC that corresponds to the brightest sprite element in F40 of Figure a.…”
Section: Discussionmentioning
confidence: 99%
“…The charge moment change (CMC), the impulsive CMC (iCMC), and the current moment waveform associated with the CG flashes [ Hu et al ., ; Cummer and Lyons , ] were reconstructed from ELF receiver measurements, by using the method presented by Mlynarczyk et al []. The ELF recordings were made by the Hylaty ELF station in Poland [ Kulak et al ., ].…”
Section: Observationsmentioning
confidence: 99%
“…Using inverse solutions developed for this purpose [29,26,25] we can determine the current and charge moments of these discharges. Each of these stations have two ferrite core active magnetic field antennas, with one oriented to observe magnetic fields along the North-South direction, and the other oriented to observe magnetic fields along the East-West direction.…”
Section: Observational Methodsmentioning
confidence: 99%